PENGARUH KUALITAS LAYANAN PENGUSAHA MANDIRI â€œYUSUF KASIMâ€ TERHADAP KEPUASAN PELANGGAN DALAM USAHA PERDAGANGAN IKAN DEMERSAL ANTAR KOTA MANADO - Daud, Juan Romel; Andaki, Jardie A.; Dien, Christian R. (Universitas Sam Ratulangi, 2016)
Abstract In carrying out the demersal fish trading business between cities many owners of capital or entrepreneurs who are less concerned about the quality of services provided to customers in various aspects. The problem formulation in this study, namely how to influence the quality of inter-city services independent entrepreneurs